Leaching behaviour of co-disposed steel making wastes: Effects of aeration on leachate chemistry and vanadium mobilisation. (November 2018) - Hobson, Andrew J.; Stewart, Douglas I.; Mortimer, Robert J.G.; Mayes, William M.; Rogerson, Mike; Burke, Ian T.
Highlights: Steel making by-products unsuitable for recycling stored in landfill. Leaching mechanism is primarily controlled by air availability. Air-exclusion led to Ca-rich, high pH leachates, with low V concentrations. Carbonate formation during aeration led to lower pH but higher V concentrations. Abstract: Steelmaking wastes stored in landfill, such as slag and spent refractory liners, are often enriched in toxic trace metals (including V). These may become mobile in highly alkaline leachate generated during weathering. Fresh steelmaking waste was characterised using XRD, XRF, and SEM-EDX. Batch leaching tests were performed under aerated, air-excluded and acidified conditions to determine the impact of atmospheric CO2 and acid addition on leachate chemistry. Phases commonly associated with slag including dicalcium silicate, dicalcium aluminoferrite, a wüstite-like solid solution and free lime were identified, as well as a second group of phases including periclase, corundum and graphite which are representative of refractory liners. During air-excluded leaching, dissolution of free lime and dicalcium silicate results in a high pH, high Ca leachate in which the V concentration is low due to the constraint imposed by Ca3 (VO4 )2 solubility limits. Under aerated conditions, carbonation lowers the leachate pH and provides a sink for aqueous Ca, allowing higher concentrations of V to accumulate. Below pH 10, leachate is dominated by periclase dissolution and secondary phases including monohydrocalcite and dolomite are precipitated. Storage of waste under saturated conditions that exclude atmospheric CO2 would therefore provide the optimal environment to minimise V leaching during weathering.